The impact of visual educational methods on enhancing the speaking skills of ninth-grade students at Al-Qadriyya Model High School, Jambar, for the academic year 2020-2021 - Rifki Yoga Pratama; Syamsul Anam; Maskud Maskud (Green Publisher Indonesia, 2024)
This research explores the impact of visual educational tools on enhancing the speaking skills of ninth-grade students at Al-Qadriyya Model High School Jambar during the academic year 2020-2021. The study employs quantitative research methods, particularly utilizing surveys to collect data. Results indicate a significant positive effect of visual educational tools, both highlighting and non-highlighting, on promoting students' speaking skills. Specific conclusions reveal a high correlation between the use of these tools and improved speaking proficiency. Recommendations are provided for teachers, students, the school administration, and future researchers to maximize the benefits of educational tools in language learning.